THE ROLE OF ATMOSPHERIC CUES IN SHAPING THE RESPONSE OF FOREIGN TOURISTS VISITING BATAM - Hepy Hefri Ariyanto (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
This research examined the role of a destination atmospheric cues on tourist' desire to engage in word of mouth (WOM) communication. It adopted the Stimulus-Organism-Response (SOR) model taken from retail theory. In implementing the model, Organism were the combination of three aspects, namely process, affective and cognitive states. Information from 393 foreign tourists visiting Batam City illustrated the power of SOR in explaining the role of atmospheric cues to forming desire WOM communication. Importantly, the results of the research also highlighted the procedural nature of the cognitive state of the organism. This research reinforced the importance of studying tourist behavior through an SOR angles and how affective and cognitive elements of organisms contributed to foreign tourist decision making